SWOT Analysis In Bumi Sawunggaling Hotel Bandung - Pranatha, Prima Setia Judha; Asshofi, Izza Ulumuddin Ahmad (Media Wisata, 2023)
At this time, Indonesia has entered the New Normal period, or adaptation of new habits is a method carried out by the Indonesian government during the global Covid-19 pandemic. So that people can continue to carry out activities as usual by implementing health protocols during a pandemic. The purpose of this study is to examine the SWOT (Strengths, Weaknesses, Opportunities, and Treats) study at the Bumi Sawunggaling hotel in Bandung, which the researcher will do as a step in exploiting the potential that exists in the Bumi Sawunggaling hotel and as an effort in increasing revenue at Hotel Bumi Sawunggaling. In this study, the method used is qualitative. The qualitative research method, as said by Sugiyono (2009:9), is a research method carried out to examine every condition of an object naturally, and researchers here are the main instrument; data collection techniques are carried out based on the results of observations and interviews.